Steroidal constituents isolated from the seeds of Withania somnifera. Issue 13 (15th June 2021) - Iguchi, Tomoki; Kuroda, Minpei; Ishihara, Mai; Sakagami, Hiroshi; Mimaki, Yoshihiro
Abstract: A new withanolide glycoside (1 ), two new ergostanol glycosides (2 and 3 ), and a new furostanol glycoside (4 ), along with nine known steroidal derivatives (5 –12 ) were isolated from the seeds of Withania somnifera . The structures of the new compounds were determined using spectroscopic analysis and hydrolysis. The cytotoxic activities of the isolated compounds were evaluated against Ca9-22 human gingival carcinoma cells, HSC-2 human mouth carcinoma cells, and HL-60 human promyelocytic leukemia cells. Only 12 exhibited cytotoxic activity against these cell lines with IC50 values of 0.38, 0.54, and 1.5 μM, respectively. Graphical Abstract: UF0001